2019
DOI: 10.31577/szausav.2019.suppl.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Eine Schrift der Reiternomaden im 1. Jt. v. Chr.? Bemerkungen zu den sogenannten skythischen Pfeilspitzen mit Markierungen zwischen Ostalpen, Ural und Anatolien

Abstract: a script of the equestrian nomads in the 1 st millennium Bc? remarks on the so-called Scythian arrowheads with markings between Eastern alps, urals and anatolia numerous studies are devoted to the distribution, chronology and historical interpretation of the so-called scythian arrowheads, which are known in the vast area between Central europe, eurasia and the near east. Less well known and researched so far is the occurrence of incised and cast signs that occur on the wings and sometimes the sockets of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…127-34;Kossack 1987;Jaszewska and Kałagate 2011). Anja Hellmuth (Hellmuth 2006b(Hellmuth , 2010 has shown that the quiver assemblages of the attackers, while having a clear Carpathian component, also included arrows from the north Pontic steppes. Interestingly, an iron blade of what is likely to be a Scythian akinakeswas recovered from a cremation grave in the stronghold's cemetery (Bukowski 1977, p. 134), indicating that there may have been times of more peaceful interaction between the stronghold's elite and steppe horsemen before the final onslaught (Bukowski 1977, p. 136, no.…”
Section: The Site Of the Hoardmentioning
confidence: 99%
See 2 more Smart Citations
“…127-34;Kossack 1987;Jaszewska and Kałagate 2011). Anja Hellmuth (Hellmuth 2006b(Hellmuth , 2010 has shown that the quiver assemblages of the attackers, while having a clear Carpathian component, also included arrows from the north Pontic steppes. Interestingly, an iron blade of what is likely to be a Scythian akinakeswas recovered from a cremation grave in the stronghold's cemetery (Bukowski 1977, p. 134), indicating that there may have been times of more peaceful interaction between the stronghold's elite and steppe horsemen before the final onslaught (Bukowski 1977, p. 136, no.…”
Section: The Site Of the Hoardmentioning
confidence: 99%
“…In the Carpathian Basin, the best-studied example of a fortification destroyed by Scythian raiding is a stronghold on a spur of the lesser Carpathian Mountains called Smolenice-Molpír in Western Slovakia (Stegmann-Rajtár 2005;Hellmuth 2006aHellmuth , 2006bMüller 2012). It was once thought to have been destroyed before the turn of the sixth century BCE (Parzinger and Stegmann-Rajtár 1988) and to have been the first Eastern Hallstatt stronghold to fall to a Scythian raid.…”
Section: Slaving Raiding Diplomatic Gifts the Hoard's Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation